1.0k views
4 votes
Please help me. It's urgent​

Please help me. It's urgent​-example-1
User Oro
by
4.8k points

1 Answer

3 votes

Answer:

a) 7/5

Explanation:


y-(y-1)/(2)=1-(y-2)/(3) \\Through\ the\ butterfly\ method\ of\ resolving\ denominators\ ,\\(2y-(y-1))/(2) = (3-(y-2))/(3) \\(2y-y+1)/(2) = (3-y+2)/(3) \\(y+1)/(2) =(5-y)/(3) \\3(y+1)=2(5-y)\\3y+3=10-2y\\3y+2y=10-3\\5y=7\\y=(7)/(5)

User Mevatron
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.